THE ANALYSIS OF STUDENT’S MISCONCEPTION OF ALGEBRA OPERATION OF 8TH STUDENT OF SMP N 2 BANTUL BY USING CERTAINTY OF RESPONSE INDEX (CRI) - Melly Ristyana; Harina Fitriyani (Universitas Ahmad Dahlan, 2018)
The misconception is a condition where a student has a misunderstanding in comprehending a particular concept of what is meant to be. It raised when a student was gaining a new concept, namely in learning math, specifically in algebra operation. To know the misconceptions can be detected by using the Certainty of Response Index (CRI). This study aims to know the students' misconceptions and their causes in algebra operation of the 8th grade of SMP N 2 Bantul. This study is qualitative research. The subject of the study is the 8th grade of class C in SMP N 2 Bantul 2016/2017. The object of the study is the student's misconceptions in algebra operation. The data collection technique is in the form of a test based on the CRI and an interview. The data analysis used reduction, data presentation, and data inversion and verification. The results show that 53% of the students know the concept of algebra operation, 20% of the students only guesting, 15% do not know the concept, and 12% have misconceptions. Within the 12%, the misconceptions can be mention as follows (1) in the concept of formulating simple algebra and fraction algebra into its factors; (2) in the concept of the operation of addition, subtraction, multiplication, and division in the form of simple algebra and fraction algebra. The causes of this misconceptions are (1a) the student's low comprehension, (1b) the student's incomplete information, (1c) the student's low motivation to learn is not fully understood yet; (2a) the wrong intuition or opinion, (2b) The student's cognitive condition that remains in concrete.